2021
DOI: 10.1017/s0022149x20001017
|View full text |Cite
|
Sign up to set email alerts
|

Helminth infections in Italian donkeys: Strongylus vulgaris more common than Dictyocaulus arnfieldi

Abstract: Donkeys have been used as working animals for transport and farm activities worldwide. Recently, in European countries, there has been an increasing interest in donkeys due to their use as pets, onotherapy or milk production. During 2014–2016, a countrywide survey was conducted to determine prevalence and risk factors of principal helminth infections in 1775 donkeys in 77 Italian farms. A questionnaire on management and parasite control practices was filled out for each farm. Faecal samples were examined using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…In this pony population, anthelmintic treatments are carried out without performing a coprological diagnosis once per year, and this anthelmintic treatment scheme is quite different from those reported in horses in Italy [ 27 ] but is very similar to that reported in the Italian donkey population [ 28 ]. Contrary to the diffusion of anthelmintic resistance worldwide [ 29 ], anthelmintic treatment with fenbendazole has been shown to be highly effective in this wild pony population, and for this reason, as reported for donkeys [ 30 ], ponies of Esperia can be considered an animal population in refugia.…”
Section: Discussionmentioning
confidence: 98%
“…In this pony population, anthelmintic treatments are carried out without performing a coprological diagnosis once per year, and this anthelmintic treatment scheme is quite different from those reported in horses in Italy [ 27 ] but is very similar to that reported in the Italian donkey population [ 28 ]. Contrary to the diffusion of anthelmintic resistance worldwide [ 29 ], anthelmintic treatment with fenbendazole has been shown to be highly effective in this wild pony population, and for this reason, as reported for donkeys [ 30 ], ponies of Esperia can be considered an animal population in refugia.…”
Section: Discussionmentioning
confidence: 98%
“…As in horses and also in donkeys, the most common nematode parasites are intestinal strongyles (large and small strongyles) (Buono et al ., 2021 ; Dias de Castro et al ., 2022 ). In both species, parasitic infections are caused mainly (>90%) by small strongyles (Buono et al ., 2021 ; Jota Baptista et al ., 2021 ; Nielsen et al ., 2021 ).…”
Section: Helminth Infections In Horses and Donkeys: Head To Head!mentioning
confidence: 99%
“…As in horses and also in donkeys, the most common nematode parasites are intestinal strongyles (large and small strongyles) (Buono et al ., 2021 ; Dias de Castro et al ., 2022 ). In both species, parasitic infections are caused mainly (>90%) by small strongyles (Buono et al ., 2021 ; Jota Baptista et al ., 2021 ; Nielsen et al ., 2021 ). A recent meta-analysis reported that Cylicocyclus nassatus , Cylicostephanus longibursatus and Cyathostomum catinatum represent about 55% of the specimens in horses (Bellaw and Nielsen, 2020 ).…”
Section: Helminth Infections In Horses and Donkeys: Head To Head!mentioning
confidence: 99%
See 2 more Smart Citations